2004
DOI: 10.1350/ijps.6.3.171.39134
|View full text |Cite
|
Sign up to set email alerts
|

Gender Discrimination and Regulatory Behaviour: An Exploratory Study in Policing

Abstract: Tim Prenzler is head of the School of Criminol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A stream of research worldwide has brought improved understanding about the roles assigned to women officers and the ways in which women are treated and evaluated by their male colleagues and supervisors (Balkin, 1988;Belknap & Shelley, 1993;Brown, 1998;Dodge, Valcore, & Gomez, 2011;Harrington & Lonsway, 2004;Heidenshohn, 1992;Kakkar, 2002;Lord, 1986;C. A. Martin, 1996; S. E. Martin, 1990;Morash & Haarr, 1995;Prenzler, 2004;Segrave, 1995;Southgate, 1981;Sun & Chu, 2008;Westmarland, 2001). Studies have also shown how the negative attitudes of male officers have been an impediment to the successful recruitment, deployment and performance of female officers (Hunt, 1990;S.…”
Section: Introductionmentioning
confidence: 99%
“…A stream of research worldwide has brought improved understanding about the roles assigned to women officers and the ways in which women are treated and evaluated by their male colleagues and supervisors (Balkin, 1988;Belknap & Shelley, 1993;Brown, 1998;Dodge, Valcore, & Gomez, 2011;Harrington & Lonsway, 2004;Heidenshohn, 1992;Kakkar, 2002;Lord, 1986;C. A. Martin, 1996; S. E. Martin, 1990;Morash & Haarr, 1995;Prenzler, 2004;Segrave, 1995;Southgate, 1981;Sun & Chu, 2008;Westmarland, 2001). Studies have also shown how the negative attitudes of male officers have been an impediment to the successful recruitment, deployment and performance of female officers (Hunt, 1990;S.…”
Section: Introductionmentioning
confidence: 99%